From the Therapist’s Couch and from the Stage to the Screen - Raúl Vaimberg (Forum for Group Psychotherapies and Processes)
This is the path we take in this article, in order to understand the changes that are taking place in human communication and in the therapeutic setting in general, and within psychoanalytical and psycho-dramatic psychotherapies in particular.Transferring word to action and moving from the theatrical stage to technological reproducibility can lead to an increase in fear, triviality and isolation, as well as to a decreased sense of subjectivity. This being said, new possibilities have become available to broadcast psychotherapy, as well. New doors are open to individual and collective unconscious transformations and to the dramatization of scenes that travel within cyberspace, helping us build meaning that is constructive. To reach these objectives in the field of psychotherapy it is necessary for there to be, on the other side of the screen, a specialized listener that can aid us in this search for broader meaning.